Alttestamentliche Wissenschaft als Theologie? - Müller, Reinhard (Zeitschrift für Theologie und Kirche, 2024)
The article discusses the perspective in which Old Testament scholarship can be regarded as theology. Introduced by remarks on Julius Wellhausen's departure from the Faculty of Theology in Greifswald in 1882, the history of Old Testament scholarship is examined by looking at 1) Hebraic studies, 2) historical criticism of the Old Testament writings, 3) research into the history of religion and the turn towards Old Testament theology. The concluding section develops the way in which Old Testament scholarship perceives itself as theology and contributes to the common task of the theological disciplines.